Examining the domains and boundaries of sexuality education: perspectives of scholars and practitioners in family life education and sex education - Kuborn, Sarah (Kansas State University, 2015)
This study investigates the domains and boundaries of sexuality education between two educational fields: sexuality education and family life education. The goal was to understand how scholars and practitioners in these fields conceptualize sexuality education. The journalistic questions of Who, What, When, For whom, and Why were identified within each field by using the constant comparative method to complete a content analysis of publications by scholars and by interviewing certified professionals in each field. Through the lens of Social Constructionism Theory and a Phenomenological Approach, this study helped clarify the similarities and differences of two professional fields, in turn, advancing each field. Results indicated that sexuality education and family life education are similar in many ways; it is the approach that each takes that makes them different. Sexuality education takes a holistic approach while family life education takes a contextual approach when teaching sexuality education. This approach, in turn, affects the rest of the education, including the domains that were identified.
Keywords: Family life education; Sexuality education; Domains and boundaries; Human sexuality; Education, General (0515); Individual & Family Studies (0628)